The General Telecommunications Law from a convergent perspective - Quelho, Renata Tonicelli de Mello (Law, State and Telecommunications Review, 2011)
This study analyzes whether the Brazilian General Telecommunications Law is adaptable to a convergence context. First, it reveals one essential feature of the Information and Communication Technologies (ICT) infrastructures that changes policy and market governance: modularity. Then, two scenarios that inhibit convergence are identified: communication policy islands and silos in the regulatory regime. Layer Regulation is presented as a way to address convergence. Facing all of these elements, the article concludes for the relative adaptability of the Brazilian telecommunication law.